‘His Own Nearer Household Gods’: Pagans, Christians, and Marius the Epicurean’s Religious Hermeneutics - Jude Wright (Cahiers Victoriens et Edouardiens)
Walter Pater’s Marius the Epicurean (1885) may be seen as part of the subgenre of the all but forgotten Historical Novel of Early Christianity, which is represented by such lights as Newman, Kingsley, and Wiseman. Yet, Pater’s novel is distinct from these others, for while it follows the familiar trajectory of works in this vein, tracing the progress of the eponymous protagonist from paganism to Christianity, Marius’s conversion is portrayed primarily as a movement across a spectrum of belief that is tied directly through aesthetics back to the pagan religiosity that Marius grew up participating in. ‘His Own Nearer Household Gods’ argues that Marius’s developing religiosity is a construct uniting Christianity and Roman paganism by foregrounding subjective aesthetic experience. The article’s central focus is on the way in which Pater’s style and narrative strategies provide the reader with a vision of reality mediated through Marius’s own aesthetic construction of the world.